Characterization of CCX282-B, an orally bioavailable antagonist of the CCR9 chemokine receptor, for treatment of inflammatory bowel disease. - Walters, M; Wang, Y; Lai, N; Baumgart, T; Zhao, B; Dairaghi, D; Bekker, P; Ertl, L; Penfold, M; Jaen, J; Keshav, S; Wendt, E; et al. (2010)
The chemokine system represents a diverse group of G protein-coupled receptors responsible for orchestrating cell recruitment under both homeostatic and inflammatory conditions. Chemokine receptor 9 (CCR9) is a chemokine receptor known to be central for migration of immune cells into the intestine. Its only ligand, CCL25, is expressed at the mucosal surface of the intestine and is known to be elevated in intestinal inflammation. To date, there are no reports of small-molecule antagonists targeting CCR9. We report, for the first time, the discovery of a small molecule, CCX282-B, which is an orally bioavailable, selective, and potent antagonist of human CCR9. CCX282-B inhibited CCR9-mediated Ca(2+) mobilization and chemotaxis on Molt-4 cells with IC(50) values of 5.4 and 3.4 nM, respectively. In the presence of 100% human serum, CCX282-B inhibited CCR9-mediated chemotaxis with an IC(50) of 33 nM, and the addition of α1-acid glycoprotein did not affect its potency. CCX282-B inhibited chemotaxis of primary CCR9-expressing cells to CCL25 with an IC(50) of 6.8 nM. CCX282-B was an equipotent inhibitor of CCL25-directed chemotaxis of both splice forms of CCR9 (CCR9A and CCR9B) with IC(50) values of 2.8 and 2.6 nM, respectively. CCX282-B also inhibited mouse and rat CCR9-mediated chemotaxis. Inhibition of CCR9 with CCX282-B results in normalization of Crohn's disease such as histopathology associated with the TNF(ΔARE) mice. Analysis of the plasma level of drug associated with this improvement provides an understanding of the pharmacokinetic/pharmacodynamic relationship for CCR9 antagonists in the treatment of intestinal inflammation.